EFEKTIVITAS PENERAPAN SOCIAL EMOTIONAL LEARNING PADA PEMBENTUKAN RASA EMPATI PESERTA DIDIK DI MI RAHMANIA ISLAMIC SCHOOL - Litakuna Karima; Nida Aulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the development of the times or 21st century learning with the development of technology which causes a lack of concern for the surrounding environment. So that students at this time still cannot form good characters, especially in empathizing. Based on pre-research, the author is interested in the existence of Social Emotional Learning at MI Rahmania Islamic School. This study aims to determine the application and effectiveness of Social Emotional Learning on the formation of empathy for students at MI Rahmania Islamic School. This research uses descriptive qualitative research. The data collection technique is by using observation, interview, and documentation methods. And data analysis techniques are carried out through data collection, data reduction, data presentation, and data verification. The results of this study indicate that the application of Social Emotional Learning in the formation of empathy for students at MI Rahmania Islamic School shows good planning, implementation, and evaluation. The formation of empathy for grade 5 students at MI Rahmania Islamic School in the cognitive aspect has been formed and seen significantly based on the results of the initial and final observation assessments on the perspective taking and fantasy components. This shows that Social Emotional Learning has been successful and quite effective in providing changes in the formation of learners' empathy.